Behavioral Assessment of Emotion Discrimination, Emotion Regulation, and Cognitive Control in Childhood, Adolescence, and Adulthood - Tottenham, Nim; Hare, Todd A.; Casey, B.J. (Frontiers in Psychology, 2011)
Emotion discrimination, emotion regulation, and cognitive control are three related, yet separable processes that emerge over the course of development. The current study tested 100 children, adolescents, and adults on an Emotional Go/Nogo task, illustrating the ability of this paradigm to identify the unique developmental patterns for each of these three processes in the context of both positive (happy) and negative emotions (fear, sad and anger), across three different age groups. Consistent with previous literature, our findings show that emotion discrimination and regulatory abilities (both cognitive control and emotion regulation) improve steadily for each age group, with each age group showing unique patterns of performance. The findings suggest that emotion regulation is constructed from basic cognition control and emotion discrimination skills. The patterns of behavior from the Emotional Go/Nogo task provide normative benchmark data across a wide range of emotions that can be used for future behavioral and neuroimaging studies that examine the developmental construction of emotion regulatory processes.